Sources of Job Related Ambiguity and Their Consequences Upon Salespersons' Job Satisfaction and Performance - Behrman, Douglas N.; Bigoness, William J.; Perreault, William D. (Management Science, 1981)
This study presents a conceptual model relating four sources of job related ambiguity and two individual difference variables (locus of control and need for clarity) to salesperson job satisfaction and job performance. Previous research related to the model is briefly reviewed. Then, drawing data from a multicompany sample of industrial salespersons and their managers, behavioral research methods are used to clarify the nature and strength of the relationships in the model. The analysis reveals that ambiguity concerning family expectations is positively related to performance, but ambiguity regarding sales manager and customer expectations is negatively related to performance. Lower levels of satisfaction are explained primarly by ambiguous managerial expectations. The individual difference variables are shown to be related to job outcomes even after adjusting for different levels of perceived ambiguity. The individual difference variables, however, do not moderate the relationships between sources of ambiguity and job outcomes.